2016
DOI: 10.5194/acp-16-5949-2016
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Bessel's method for solar eclipses prediction in the WRF-ARW model

Abstract: Abstract. Solar eclipses are predictable astronomical events that abruptly reduce the incoming solar radiation into the Earth's atmosphere, which frequently results in nonnegligible changes in meteorological fields. The meteorological impacts of these events have been analyzed in many studies since the late 1960s. The recent growth in the solar energy industry has greatly increased the interest in providing more detail in the modeling of solar radiation variations in numerical weather prediction (NWP) models f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…The Advanced Research WRF (WRF-ARW) is a state-of-the-art open source mesoscale atmospheric model, developed by National Center for Atmospheric Research (NCAR) for both research and numerical weather prediction purposes (Powers et al, 2017). This model, which is probably the most popular meteorological (it also has a climatic version) model worldwide, has the capability to be used for a wide range of applications, such as real-time numerical weather prediction, data assimilation, parameterized-physics research, regional climate simulations, air quality modeling, atmosphere-ocean coupling, and idealized simulations (Blossey et al, 2013;Doubrawa et al, 2018;Jimenez et al, 2016;Lin et al, 2015;Moeng et al, 2007;Montornès et al, 2016;Wang et al, 2009;Yamaguchi & Feingold, 2012;Zhong et al, 2016). In addition, it can be ran at different domains and offers various options for parameterization of convective processes, turbulent transports, evolution of surface temperature and soil moisture, and soil-air interactions (Ruiz-Arias et al, 2013;Skamarock et al, 2008).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The Advanced Research WRF (WRF-ARW) is a state-of-the-art open source mesoscale atmospheric model, developed by National Center for Atmospheric Research (NCAR) for both research and numerical weather prediction purposes (Powers et al, 2017). This model, which is probably the most popular meteorological (it also has a climatic version) model worldwide, has the capability to be used for a wide range of applications, such as real-time numerical weather prediction, data assimilation, parameterized-physics research, regional climate simulations, air quality modeling, atmosphere-ocean coupling, and idealized simulations (Blossey et al, 2013;Doubrawa et al, 2018;Jimenez et al, 2016;Lin et al, 2015;Moeng et al, 2007;Montornès et al, 2016;Wang et al, 2009;Yamaguchi & Feingold, 2012;Zhong et al, 2016). In addition, it can be ran at different domains and offers various options for parameterization of convective processes, turbulent transports, evolution of surface temperature and soil moisture, and soil-air interactions (Ruiz-Arias et al, 2013;Skamarock et al, 2008).…”
Section: Model Descriptionmentioning
confidence: 99%
“…5, is plotted against r. Solar limb darkening is most significant at the shortest wavelengths, for which the difference between the hot centre and relatively cooler limb is most pronounced (see also Fig. 5 of Ockenfuß et al, 2020). Figure 6 is a sketch of the lunar disc occulting the solar disc during an annular solar eclipse.…”
Section: Obscuration Fractionmentioning
confidence: 99%
“…They showed that the error in the solar irradiance close to total obscuration may become 30 % at 1500 nm and 60 % at 310 nm if solar limb darkening is not taken into account. Emde and Mayer (2007), Kazantzidis et al (2007), and Ockenfuß et al (2020) performed extensive 3-D radiative transfer modelling of total solar eclipses, taking into account solar limb darkening. Their work gives insight into the spectral behaviour of sunlight reaching a ground sensor located in or close to the total Moon shadow and the importance of the various 3-D radiative transfer components.…”
Section: Introductionmentioning
confidence: 99%
“…To further explore the impacts of the 2017 total solar eclipse and for comparison with observations, the WRF Model (Skamarock et al 2008), version 3.7.1, was utilized. This version was specifically adapted for the study of the evolution of the atmosphere during solar eclipses (Montornès et al 2016). A 30-h simulation from 0000 UTC 21 August to 0600 UTC 22 August 2017 was conducted with and without the presence of the eclipse (i.e., without and with solar forcing, respectively).…”
Section: The Weather Research and Forecasting Model Applicationsmentioning
confidence: 99%